MULTIKULTURALISME MASYARAKAT DESA KADINDI KECAMATAN PEKAT KABUPATEN DOMPU (STUDI INTERAKSI DAN SOLIDARITAS) - Lalu Rumasih (SOSIO EDUKASI Jurnal Studi Masyarakat dan Pendidikan, 2019)
Talking about the multiculturalism of the Kadindi community, the majority of the people are Muslim, besides Islam, there is also Hinduism, with a variety of traditional cultures that they profess and exalted are characteristic of the local community. Seeing the diversity of religions, Kadindi's culture which has always lived side by side and peacefully because the people uphold the tolerance of religion and culture adopted is unique, even though the Kadindi Village community is a multicultural society, but the community maintains social interaction and maintains social solidarity well . This study aims to determine the multiculturalism of the Kadindi Village community and to determine the interaction and solidarity of the Kadindi Village community in the Pekat District of Dompu Regency. This study uses a qualitative approach to the type of descriptive research. Descriptive research is a series of activities in order to obtain data or information that is true and provides a thorough and in-depth understanding. Data collection techniques used are observation, interviews and documentation. While the data analysis technique used is interactive model qualitative data analysis through the stages of data reduction, data presentation, and data verification.